Lives lived differently: Geography and the study of black women - Daley, P (Wiley, 2020)
This paper considers the geographical study of black women’s lives through a reflection on Jacqueline Tivers’ (Area, 10, 1978, 302) “How the other half lives: the geographical study of women.” While feminist geographers have drawn on black feminist thought, the limited presence of black women academics within the discipline of Geography contributed to a lack of sensitivity to the distinctiveness of black women’s geographies. The paper notes the considerable body of work that has emerged since Tivers’ paper, including that which challenges the universalisation of concepts of women, gender, family, and the household, especially in relation to black women’s lives globally. It asserts the globality of black women’s “lifeways” – especially the interconnections between continental Africa and the African diaspora – and suggests that a more relational approach to the study of black women’s lives could inform geographers’ understanding of gendered and racial structures of oppression and alternative geographies of resistance and freedom.